2000
DOI: 10.1093/gerona/55.7.m393
|View full text |Cite
|
Sign up to set email alerts
|

Pain Factors Associated With Physical Disability in a Sample of Community-Dwelling Senior Citizens

Abstract: A thorough pain evaluation and appropriate management of certain aspects of pain may aid in the independent functioning of elderly persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
2
12

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 30 publications
4
59
2
12
Order By: Relevance
“…In individuals older than 65 years, osteoarthritis of the knees or hands and rotator cuff disease are the most prevalent causes of musculoskeletal pain. A high prevalence of these degenerative musculoskeletal diseases has been reported [23], and prevalence of concurrent upper and lower extremity pain in patients older than 65 years is reportedly greater than 40% [25]. Furthermore, musculoskeletal pain or disability is reportedly more prevalent [18] and more severe in women [8], which concurs with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…In individuals older than 65 years, osteoarthritis of the knees or hands and rotator cuff disease are the most prevalent causes of musculoskeletal pain. A high prevalence of these degenerative musculoskeletal diseases has been reported [23], and prevalence of concurrent upper and lower extremity pain in patients older than 65 years is reportedly greater than 40% [25]. Furthermore, musculoskeletal pain or disability is reportedly more prevalent [18] and more severe in women [8], which concurs with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…The morbidity was, however, in general low, with gradually increasing morbidity if LBP was associated with sciatica and neurological deficits. The 46 % one-year prevalence of LBP in our old male population is somewhat high in the perspective of the reported prevalence of 13-49 % in other reports [11][12][13][14][15]. It is, however, difficult to directly compare results since there is no well-established definition of LBP.…”
Section: Discussionmentioning
confidence: 59%
“…We have found that the ACR classification of widespread pain provides a sound method for classifying the most disabling pain that causes quantitatively different risks for older persons compared to lower extremity pain or mild musculoskeletal pain in 1 joint area. Prior studies have shown that location and severity of pain are key pain characteristics that are associated with disability (Lichtenstein et al, 1998;Scudds and Robertson, 2000). In addition, more severe joint pain is associated with multisite pain (Leveille et al, 1998;Vogt et al, 2003;Croft et al, 2005) and multisite pain is more disabling than other pain (Hopman-Rock et al, 1997;Leveille et al, 2001).…”
Section: Discussionmentioning
confidence: 99%